2018
DOI: 10.1186/s12967-018-1453-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of adiponectin gene variants with idiopathic recurrent miscarriage according to obesity status: a case–control study

Abstract: BackgroundThis study addresses whether the association of adiponectin gene (ADIPOQ) variants with idiopathic recurrent pregnancy loss (RPL) is influenced by obesity.MethodsRetrospective case–control study performed in outpatient obstetrics/gynecology clinics. Study subjects comprised 308 women with RPL, defined as ≥ 3 consecutive miscarriages of unknown etiology, and 310 control women. ADIPOQ genotyping was done by allele exclusion method on real-time PCR.ResultsOf the 14 ADIPOQ variants tested, the minor alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Therefore, preeclamptic -11377GG genotype carriers are likely to express low levels of adiponectin, resulting in impaired control of glycemia. Also, −11377G allele carriers have been associated with chronic hypertension (Ong et al, 2010), recurrent pregnancy loss (Dendana et al, 2018), and gestational diabetes (Pawlik et al, 2017) in non-Latin American populations.…”
Section: Gene Variants Involved In Metabolic Processesmentioning
confidence: 99%
“…Therefore, preeclamptic -11377GG genotype carriers are likely to express low levels of adiponectin, resulting in impaired control of glycemia. Also, −11377G allele carriers have been associated with chronic hypertension (Ong et al, 2010), recurrent pregnancy loss (Dendana et al, 2018), and gestational diabetes (Pawlik et al, 2017) in non-Latin American populations.…”
Section: Gene Variants Involved In Metabolic Processesmentioning
confidence: 99%
“…Adiponectin (AdipoQ) is a 30 KDa adipokine encoded by the AdipoQ gene, mostly produced by adipocytes and is rich in human plasma ( Dendana et al, 2018 ). AdipoQ is recognized to enhance the insulin susceptibility of target organs including muscles and liver, finally controlling fatty acid metabolism and peripheral glucose levels ( Hotta et al, 2001 ; Yamauchi et al, 2001 , 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, TG carriers were more in HIV-1 ART-naive ISUs compared with -experienced suggesting that ADIPOQ haplotypes could be influencing disease outcomes in HIV-1 ISUs. Previous studies have reported ADIPOQ haplotypes modulating obesity and type 2 diabetes ( 31 ). There is limited data on ADIPOQ haplotype modulation of disease outcomes in infectious diseases including HIV-1.…”
Section: Resultsmentioning
confidence: 97%
“…Rate of GC carriage was lower in the -naive compared to -experienced ISUs. In contrast, TG carriers were more in HIV-1 ART-naive ISUs compared with -experienced suggesting that ADIPOQ haplotypes could be influencing disease (31). There is limited data on ADIPOQ haplotype modulation of disease outcomes in infectious diseases including HIV-1.…”
Section: Discussionmentioning
confidence: 99%